Precautionary measures. Conditions, seizure report - Bucur, Ana Maria (Technium Social Sciences Journal, 2023)
The recovery of property and damage generally caused by criminal offences plays an important role in the judicial economy because imposing effective and timely measures can achieve beneficial consequences both in terms of disrupting criminal activity, reducing the capacity to carry out new criminal activities, but also in terms of strengthening society's confidence, as a rule, on the fact that crime cannot escape control and is effectively eradicated. Lately, international cooperation at the level of competent bodies has been reflected not only in the adoption of conventions or directives in combating serious crimes such as money laundering, organized crime, terrorism or corruption, but also in the creation of mechanisms to allow the rapid transmission of information and the imposition as soon as possible of the necessary measures to block criminal benefits as soon as possible. Criminal law enforcement and criminal procedural authorities must pay particular attention to tracing, identifying and evaluating, seizing assets in order to take precautionary measures from the first moments of starting the investigation. Placing the activity of repairing damage and recovering the proceeds of crime on a secondary level and not on the same level as the activity of tracking down and catching the persons who committed the crime, inevitably leads to its failure because criminals are given the necessary time to seize their assets, after learning that their criminal activity has been discovered. Without the application of precautionary measures, any financial investigation shall be devoid of purpose unless a measure is taken to freeze the property concerned, to avoid any further disposal of property and diminution of the assets of the person who committed the offence causing damage.